Exacerbation during the first year of treatment affects lung function in subjects with asthma – a 10-year follow-up - Almeida, Pca; Ponte, Ev; Stelmach, R; Harrison, Tw; Scichilone, N; Souza-Machado, A; Cruz, Aa (The Journal of asthma, 2025)
Inhaled corticosteroids (ICS) are the preferred treatment for asthma. They improve symptoms and reduce exacerbations and deaths, but their long-term impact on lung function loss remains unclear, especially after delayed treatment. We aimed to characterize the lung function trajectories in subjects with previously untreated severe asthma. The secondary aim was to identify predictors of FEV decline, and future exacerbations. This is a analysis that followed 184 subjects with asthma for 10 years after a delayed start of regular maintenance ICS treatment. Absolute lung function variation was calculated using two different baselines: (i) FEV after one year of regular treatment (V ) and (ii) best FEV observed any time before the final visit. Most individuals were female (84%) over 50 years old and had early-onset asthma with a median of 30 years without regular ICS treatment. Ninety-nine (54%) had an FEV1 decline above 25ml/year, using strategy (i). Those subjects were younger, had shorter duration of asthma, and had better lung function at V . Most of the participants without any obstructive pattern (74%) or with mild obstruction (64%) at V showed a faster absolute FEV decline, however PRISm showed faster relative decline than the other groups. This study showed improved symptoms and quality of life with variable lung function trajectories among individuals with asthma who start regular treatment after decades of delay. Additionally, exacerbation during the first year was a strong predictor of absolute FEV decline and future exacerbations, while time without treatment was a predictor of relative reduction of FEV .